Transformation of The Role of Teachers in Building Students' Critical Literacy through Contextual Learning at SMP N 3 Teras - Danarsih, Leni Yulaikah; Maksum, Muh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to describe the transformation of teachers' roles in developing students' critical literacy through contextual learning at SMP N 3 Teras. The transformation of teachers' roles has become crucial in line with the demands of 21st-century education, which emphasizes critical thinking skills as a basic competency for students. Teachers function not only as conveyors of information but also as facilitators, mediators, and developers of learning environments that encourage students to explore, analyze, and reflect deeply on information. Contextual learning is implemented as an approach that connects subject matter with the realities of students' lives, thus encouraging active engagement and meaningful understanding. Through strategies such as reflective discussions, real-life problem solving, and collaborative projects, teachers strive to build students' abilities in identifying real-life issues, evaluating arguments, and drawing logical conclusions. This study applies a qualitative approach with descriptive methods. Data were collected through observations, in-depth interviews with the literacy coordination teacher and several students, and document collection. The location of this study was in the seventh grade of SMP N 3 Teras. Teachers' success in developing critical literacy through contextual learning is influenced by several factors, including teacher pedagogical competence, school environmental support, availability of learning resources, student readiness, and collaboration between teachers and the school. The findings of this study are expected to contribute to the development of more innovative learning practices oriented towards strengthening students' critical literacy.